Quality of qualitative research in the health sciences: Analysis of the common criteria present in 58 assessment guidelines by expert users. (January 2016) - Santiago-Delefosse, M.; Gavin, A.; Bruchez, C.; Roux, P.; Stephen, S.L.
Abstract: The number of qualitative research methods has grown substantially over the last thirty years, both in social sciences and, more recently, in health sciences. This growth came with questions on the quality criteria needed to evaluate this work, and numerous guidelines were published. These guidelines, however, include many discrepancies, both in terms of vocabulary and structure. Many expert evaluators also decry the absence of consensual and reliable evaluation tools. To address this gap, we present the results of an evaluation of 58 existing guidelines in four major health science fields (medicine and epidemiology; nursing and health education; social sciences and public health; psychology/psychiatry, research methods and organization) by expert ( n = 16) and peer ( n = 40) users (e.g., article reviewers, experts allocating funds, editors). This research was conducted between 2011 and 2014 at the University of Lausanne in Switzerland. Experts met during three workshops spread over this period. A series of 12 consensual essential criteria, along with definitions, stemmed from a question in a semi-qualitative evaluation questionnaire that we developed. Although there is consensus on the name of the criteria, we highlight limitations on the ability to compare specific definitions of criteria across health science fields. We conclude that each criterion must be explained to come to broader consensus and identify definitions that are easily operational and consensual to all fields examined. Highlights: This research was conducted at the University of Lausanne between 2011 and 2014. 58 guides of criteria on the quality of the qualitative research were selected. 16 experts and 40 peer users assessed the guides with our questionnaire. We identified 12 consensual essential criteria and their associated definitions. The target audience is experts, reviewers, researchers, ethics/funding committees.